2014
DOI: 10.2147/ijgm.s42187
|View full text |Cite
|
Sign up to set email alerts
|

Management of cancer pain: 1. Wider implications of orthodox analgesics

Abstract: In this review, the first of two parts, we first provide an overview of the orthodox analgesics used commonly against cancer pain. Then, we examine in more detail the emerging evidence for the potential impact of analgesic use on cancer risk and disease progression. Increasing findings suggest that long-term use of nonsteroidal anti-inflammatory drugs, particularly aspirin, may reduce cancer occurrence. However, acetaminophen may raise the risk of some hematological malignancies. Drugs acting upon receptors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Postoperative mu agonists, playing the role as both “fertilizer” and “pesticide” for the “seed” CTCs, can protect and enhance the proliferation and function of CTCs during perioperative period. 8 Vitro studies indicated that mu agonists could increase the number of CTCs by accelerating cell cycle progression and cancer cell replication and by inhibiting apoptosis. 33 Moreover, mu agonists could promote CTCs on the function of invasiveness and metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative mu agonists, playing the role as both “fertilizer” and “pesticide” for the “seed” CTCs, can protect and enhance the proliferation and function of CTCs during perioperative period. 8 Vitro studies indicated that mu agonists could increase the number of CTCs by accelerating cell cycle progression and cancer cell replication and by inhibiting apoptosis. 33 Moreover, mu agonists could promote CTCs on the function of invasiveness and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“… 7 What is more, it has been reported that morphine may promote cell cycle progression, angiogenesis, and metastasis, and inhibit apoptosis through binding to mu-opioid receptor (MOR). 8 Otherwise, opioids also depress host immunity and alter neuroendocrine system function. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Morphine and tamoxifen co-treatments are given after surgeries or in the case of severe cancer pain (27). Otherwise, codeine and/or paracetamol are widely prescribed (8). In human, these two compounds are metabolized by the same CYPs (6D6/3A4) and UGTs (1A10, 1A4, 1A8, 2B7, and 2B15) (28, 29) as tamoxifen and might have a more complex impact on tamoxifen metabolic pathways (30,31).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Cancer-associated pain resulting from metastases, anticancer treatment or surgery represents a major problem that is treated with analgesic drugs including morphine, codeine, and/or paracetamol (8). Morphine remains the gold standard for moderate and severe pain relief despite side effects that limit its chronic use (9).…”
Section: Introductionmentioning
confidence: 99%